ASSA14-11-01 Decreased the Expressions of Soluble VEGFR2 and SOD in Hypertensive Diabetic Patients. (1st December 2014) - Yu, S; Jian, L; Song, Z; Qian, X; Chen, L
Abstract : Objective: To evaluate the expressions of soluble vascular endothelial growth factor receptor 2 (sVEGFR2) and superoxide dismutase (SOD) in plasma of hypertensive diabetic patients. Methods: In this cross-sectional study, fifty-seven cases were enrolled, which were divided into hypertensive diabetic group (n = 31) and control group (n = 26). Blood pressure (BP) was obtained from each participant with mercury sphygmomanometer. The expressions of sVEGFR2 and SOD were measured by ELISA. Serum lipid profile, glucose and glycosylated haemoglobin A1C (GHbA1c) levels were detected. Results: The levels of total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C), body mass index (BMI), waist circumference were significantly higher in the hypertensive diabetic group than those in control group (p < 0.05). The mean plasma levels of sVEGFR2 and SOD in hypertensive diabetic group were significantly decreased compared to that in the normal group (p < 0.05). There was a significantly positive correlation between sVEGFR2 and SOD in the whole study population ( r = 0 .289, p < 0.05). Conclusions: Soluble VEGFR2 and SOD expressions are decreased in hypertensive diabetic patients. This study indicates that decreased SOD expression may contribute to the reduction of sVEGFR2. Angiogenesis in these patients is impaired. So sVEGFR2 in plasma may be used as a biomarker to assess angiogenesis impairment in patients with hypertension and diabetes.